Practical Approaches and Advances in Spatial Tools to Achieve Multi-Objective Marine Spatial Planning - Lombard, Amanda T.; Ban, Natalie C.; Smith, Joanna L.; Lester, Sarah E.; Sink, Kerry J.; Wood, Spencer A.; Jacob, Aerin L.; Kyriazi, Zacharoula; Tingey, Richard; Sims, Helena E. (Frontiers in Marine Science, 2019)
Marine Spatial Planning (MSP) processes seek to better manage ocean spaces by balancing multiple objectives across ecological, social and economic objectives. To meet this challenge, MSP approaches and tools have evolved globally, from local to national scales. During two International Marine Conservation Congresses in 2016 and 2018, MSP practitioners and researchers from diverse geographies and socio-economic contexts met to share advances in practical approaches and spatial tools to achieve multi-objective MSP. Here we share the commonalities that emerged from studies conducted in Belize, Canada (British Columbia), South Africa, Seychelles, the United Kingdom and the USA (California). We identify seven practical approaches that we believe are broadly relevant to any multi-objective MSP process: (1) indigenous and local knowledge should inform planning goals and objectives; (2) transparent and evidence-based approaches can avoid conflict and build trust and legitimacy; (3) simple ecosystem service models and scenarios can facilitate multi-objective planning; (4) trade-off analyses can balance diverse objectives; (5) ecosystem service may assist planning for high value-data poor Blue Economy sectors; (6) game theoretic decision rules can help to deliver fair, equitable and win-win spatial allocation solutions; and (7) strategic mapping products can facilitate decision making amongst stakeholders from different sectors.